Olfactory Reference Syndrome - A Case Report - Roni Subagyo; Verlinda Irbah Fortuna; Nguamay Prima Izzata; Muhammad Syahri Romadhon; Cantika Resti Mustikasari; Mutiara Nurhardiyati Rahayu (Jurnal Psikiatri Surabaya, 2026)
Introduction: Olfactory Reference Syndrome (ORS) is a rare, under-recognized, and understudied psychiatric condition characterized by a persistent belief about the perceived odor, ideas of reference, and engagement in repetitive cleansing behaviors. The condition causes significant psychological distress, leading to social withdrawal, impaired occupational functioning, and, in severe cases, complete isolation. Greater clinical awareness and accurate diagnosis are essential to ensure appropriate psychiatric intervention and improve patient outcomes. Methods: The method of writing a case report is based on direct observation of the patient’s condition at the Bhayangkara Hospital, Kediri, in 2024 during the treatment period. Case: This report discusses a 21-year-old patient who has experienced a persistent belief that he smells and is being avoided by others for the past 9 months. The patient said that people around him liked to cover their noses when they were near him. The patient often took a shower 5 times a day because he continued to feel smelly. The patient was prescribed lorazepam 0.5 mg two times a day as an antidepressant and anti-insomnia agent. Conclusion: In patients with Olfactory Reference Syndrome (ORS), symptoms that appear include preoccupation with unpleasant body odor, delusional beliefs about the impact of the odor on other people’s judgments, and compulsive behavior such as frequent bathing or using deodorant to overcome these concerns. In this case, the patients are included in the symptoms of Olfactory Reference Syndrome (ORS). The administration of a combination of antipsychotic and antidepressant therapy in this patient showed significant improvement in symptoms.